Rekonstruksi Paradigma dan Implementasi Misi Gereja Masa Kini di Indonesia - Kalis Stevanus (STT Iman Jakarta, 2021)
The relationship between evangelism and social care is a hot topic that is still being debated. Some argue that the Church should only work on evangelism, that is, on eternal salvation (spiritual matters), not on social issues. Others are of the view that working on social issues is a means for the purpose of evangelizing. By using a descriptive qualitative approach, this article is intended: firstly to show that the mission of the Church is an integrative-holistic mission covering the field of evangelism and social service. The two are united in Missio Dei. Second, in order to attract reflections for churches everywhere, it is necessary to reconstruct the paradigm and implementation of the Church's mission in the present. The results of the discussion conclude that the Church's mission should be integrative-holistic. This means that the Church does not separate (dualism) between evangelism and social care. The integrative-holistic mission is considered very relevant and needed as an answer to bring the gospel of Jesus Christ into reality and at the same time can alleviate the problems or conditions of the society in which the Church is located.